Transition from hospital to home following pediatric solid organ transplant: Qualitative findings of parent experience. (12th May 2014) - Lerret, Stacee M.; Weiss, Marianne E.; Stendahl, Gail; Chapman, Shelley; Neighbors, Katie; Amsden, Katie; Lokar, Joan; Voit, Ashley; Menendez, Jerome; Alonso, Estella M.
Abstract Transplant providers are challenged to determine appropriate interventions for patients and families due to limited published research regarding the context of the post‐discharge experience from the perspective of parents of transplanted children. The purpose of this study is to describe the parent perspective of the transition from hospital to home following their child's solid organ transplant. Within a mixed‐methods design, 37 parents of pediatric heart, kidney, and liver transplant recipients from three pediatric hospitals responded to qualitative interview questions on the day of hospital discharge and three wk following hospital discharge. Insight to the discharge preparation process revealed necessary education components. Post‐discharge themes were identified for coping, knowledge, and adherence. The parents' responses provide awareness as to specific stressors and concerns parents are faced with when their child is discharged from the hospital after solid organ transplant and opportunities for ways the transplant team can provide support.